Libya and the future of the responsibility to protect: African and European perspectives - Dembinski, Matthias; Reinold, Theresa (2011)
Abstract: "UN Security Council Resolution 1973 and the ensuing NATO-led operation in Libya indicate, on the one hand, that the idea of humanitarian invention is still alive. In fact, it was the first instance in which the Security Council authorized the use of force against the will of the acting government of a functioning state. On the other hand, the international reaction to these events shows that the meaning of the underlying concept of a responsibility to protect (R2P) remains contested. This report discusses the impact of the Libya intervention on the perceptions held by regional actors – the European Union and African Union - toward the concept of R2P. The authors warn that these events might reinforce existing normative frictions and argue that the EU should act according to the principle of local ownership." (author's abstract)